Subchronic Administration of High-dose Monosodium Glutamate Causes Spatial Memory Dysfunction and Structural Deficits of Rat Hippocampus - Muchtar Hanafi; Faizal Muhammad; Amilia Ramadhani; Nurlaela; Zaenal Muttaqien Sofro; Ginus Partadiredja (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The toxicity of high concentration monosodium glutamate (MSG) has become a controversial issue because of its inconsistent results in human and animal studies. This present study aims to evaluate the effect of subchronic high-doses oral administration of MSG on spatial memory performance and hippocampal pyramidal cells number. Methods: This study involved twenty-eight male Wistar rats, which were divided into a control group of NaCl 0.9% and three intervention groups of MSG 1.0 mg/g bodyweight (M1), 2.0 mg/g bodyweight (M2), and 4.0 mg/g bodyweight (M3) for 30 days. Statistical analysis used a One-way ANOVA test. Results: The result showed significant differences in spatial memory on the Morris Water Maze (MWM) test, including path length (p = 0.020) and escape latency (p = 0.011) according to general linear model repeated measurement analysis. The mean difference of estimated hippocampal pyramidal cells total number among the groups showed volume (p = 0.001), numerical density (p = 0.590), and cells number (p = 0.004). Furthermore, Post-Hoc analysis in both spatial memory and hippocampal pyramidal cells showed that the increasing MSG dose from 1.0 to 4.0 mg/g bodyweight led to a decrease in the results of spatial memory performance on the MWM test and a decrease in hippocampal cells. Conclusion: The present study has provided novel quantitative data that subchronic administration of high-dose MSG caused deleterious effects on the spatial memory function and the volume and number of hippocampal pyramidal cells.